Bonding stability of a novel nano-zirconia and commercial veneering ceramics - Ahlam Almoualimy,; Yew, Hsu Zenn; Jasmina Qamaruz Zaman,; Norziha Yahaya,; Andanastuti Muchtar, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Nano-zirconia is commonly used in dentistry as a framework material over which feldspathic porcelain is layered to form an aesthetic and strong bi-layered restoration. Sufficient bonding strength between zirconia frameworks and veneering porcelains is crucial for the longevity of zirconia-based dental restorations. This study aims to determine the shear bond strength (SBS) of a colloidal-processed slip-casted novel nano-zirconia (NZ) and veneering ceramics, namely Cercon® Ceram Kiss (CK), VITA VM®9 (VM9), and IPS e.max® Ceram (e. max). Twenty-four cylindrical samples of each NZ and CZ were prepared and veneered with the veneering ceramics. Six groups of core–veneer assemblies, which are denoted as NZ-CK, NZ-VM9, NZ-e. max, CZ-CK, CZ-VM9, and CZ-e. max, were prepared for shear bond testing using the universal testing machine. Results of the shear test showed that NZ-VM9 recorded the highest shear strength value of 149.48 MPa, whereas NZ e. max showed the lowest SBS value of 71.56 MPa. A similar trend was also observed in the CZ groups, with the highest mean bonding strength (123.38 MPa) when bonded to VM9 (CZ-VM9), while the lowest mean value (44.07 MPa) was registered by the CZ-e. max groups. Scanning electron micrographs revealed that groups with high core–veneer bond strength values mostly displayed cohesive failure. By contrast, a mixed-mode of adhesive and cohesive failures was observed in the low SBS groups. The NZ showed similar performance based on the bonding property analysis. Therefore, NZ could potentially be used as an alternative to CZ.